2022
DOI: 10.3390/cells11071208
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Secreted Proteins from Prepubertal Ovarian Tissues Exposed In Vitro to Cisplatin and LH

Abstract: It is well known that secreted and exosomal proteins are associated with a broad range of physiological processes involving tissue homeostasis and differentiation. In the present paper, our purpose was to characterize the proteome of the culture medium in which the oocytes within the primordial/primary follicles underwent apoptosis induced by cisplatin (CIS) or were, for the most part, protected by LH against the drug. To this aim, prepubertal ovarian tissues were cultured under control and in the presence of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 57 publications
1
0
0
Order By: Relevance
“…In a recent study, Marcozzi et al characterized proteins involved in oocytes depletion following Cisplatin with or without LH by analyzing culture medium of prepubertal ovarian tissues following treatment. In this study, they confirmed the relevance of LH action on prepubertal ovarian tissues exposed in vitro to Cisplatin and LH and provided novel information about the proteins involved in the apoptotic reaction to Cisplatin [128].…”
Section: Prevention Of Chemotherapy-induced Ovarian Damagesupporting
confidence: 74%
“…In a recent study, Marcozzi et al characterized proteins involved in oocytes depletion following Cisplatin with or without LH by analyzing culture medium of prepubertal ovarian tissues following treatment. In this study, they confirmed the relevance of LH action on prepubertal ovarian tissues exposed in vitro to Cisplatin and LH and provided novel information about the proteins involved in the apoptotic reaction to Cisplatin [128].…”
Section: Prevention Of Chemotherapy-induced Ovarian Damagesupporting
confidence: 74%